KOMUNIKASI KEBIJAKAN PIMPINAN DALAM PENGAMBILAN KEPUTUSAN DI PESANTREN MODERN TA’DIB AL SYAKIRIN MEDAN - Muhammad Iqbal; Suriya Jaya; Mesiono Mesiono (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
This study aims to determine how the implementation of leadership communication in decision-making policies at the modern Islamic boarding school Ta'dib Al-Syakirin Titi Kuning Medan. This study uses a qualitative research method of policy analysis. Data were collected by observation, in-depth interviews, and documentation. The findings of this study are a. Communication at the Modern Islamic Boarding School Ta'dib Al-Syakirin Medan; b. Leadership at the Modern Islamic Boarding School Ta'dib Al-Syakirin Medan; c. Decision Making Policy at the Modern Islamic Boarding School Ta'dib Al-Syakirin Medan;